Digitizing Master Engineering Documents - Rina Wijayanti; Gancar Candra Premananto (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The main function of division Master Engineering Documents of the Design and Development Department is to store and maintain technical documents for all PGs. The work will increase every year, the documents stored will also continue to grow. The large number of documents in the form of hard files stored in the “Dokumen Teknik Induk” building makes it difficult for staff in the management process, both when searching for documents and maintaining them. In the document management process, it is necessary to have a master data that can accommodate all soft file documents. In addition to facilitating the process of data maintenance and document management, the existence of a master data document in the form of a softfile will make it easier for staff during the document search process according to user needs, the data distribution process will also become more effective. "Digitizing Master Engineering Documents" application is intended to convey aspirations / complaints about problems in the need of engineering documents in PT Petrokimia Gresik stakeholder environment. Archive digitization is a digital document storage system. Because it is done digitally, e-archive is done using technology such as computers, recording devices, servers, and other devices. The development of the world of information and communication technology (ICT) today has brought the world into industry 4.0. This era is marked by the abundance of data and information, cyber physical systems, to the management of big data. For information workers including archivists this is something that must be anticipated from the start because the landscape can be completely different from what exists today.